Not Another Polar Bear: Exploring Emotional Detachment from Water-Related Climate Change Risks through Participatory Art - Hemesath,Carolin Antonia Rebecca (2025)
Some forests are burning in the US, the North of Italy gets flooded, and early spring days start to feel like midsummer. But it seems more important what kind of lunch to have for Tuesday, or which coffee blend is best for the new espresso machine. What makes people really care about climate change, not just in terms of awareness, but emotionally? This thesis aims to explore the motifs behind and the ways emotional detachment in Western states from climate change related risks is done. In addition, it is exploring how participatory art can help to gather meaningful insights into naturalized cultural values that explain for in which way and why this emotional detachment is being socially constructed. By using the immersive and interactive exhibition “Water is Coming” at the Danish Architecture Centre in Copenhagen, this research examines visually expressed perspectives, meanings, and emotions towards climate change, expressed through drawings from the exhibition’s visitors. Through an explorative and multi-methodological approach, the study contextualizes and captures how visitors reflect on water-related climate risks, as presented by the exhibition’s media. By including diverse frameworks, it draws on trending concepts in climate change communication, environmental philosophy, and risk perception to contextualize the analytical insights. As the analysis has shown, the exhibition’s visitors use several tools of denial and detachment to create a safe space for reflection and stick collectively to their socially constructed norms. However, the duality and complexity of their emotional responses show in their ways of expressing criticism to human behavior on the environment, seeing hope in the doom, developing new ideas for climate risk adaptation, and showing the longing for a closer bond of humanity and nature. This research reflects on the role of media and communication in addressing climate engagement, not just through the bare representation of emotionally packed visuals, but through the imaginative and participatory act of drawing by letting the participants be the authors of their own climate narratives and finding emotional benefits in this kind of deep reflection. While being rooted in media and communication studies, this research invites researchers in this field, but also museums, exhibition designers, or decision makers in local governments to consider this kind of approach to visualize individual stories and acknowledge the power of this low-barriered entry point to social engagement. Ultimately, this thesis aims for more collaborative and creative approaches to facing the communicative challenges in climate change and other disciplines that aim to foster an inclusive approach to social transformation for the good.
Keywords: Climate change; Environmental communication; Water; Risks; Participatory art; Collaborative approaches; Emotional detachment; Implicatory denial; Normalcy bias